Pharmacist-Physician Collaboration for Diabetes Care: Cardiovascular Outcomes. (November 2013) - Howard-Thompson, Amanda; Farland, Michelle Z.; Byrd, Debbie C.; Airee, Anita; Thomas, Jeremy; Campbell, Jennifer; Cassidy, Regina; Morgan, Timothy; Suda, Katie J.
Background: Only 23% of patients are meeting all goals for cardiovascular complications of diabetes.Objective: The purpose of our study is to evaluate the effect of a pharmacist-physician collaboration on attainment of cardiovascular-related goals in patients with type 2 diabetes.Methods: This prospective, multicenter cohort enrolled patients from 7 practice sites that were members of the University of Tennessee Pharmacist Practice Based Research Network (UT Pharm Net). Patients were included if they were diagnosed with type 2 diabetes, at least 18 years of age and English speaking. Pregnant patients were excluded. Patients were followed for 12 months after enrollment. Primary cardiovascular outcomes included reduction in systolic blood pressure, diastolic blood pressure, and low-density lipoprotein (LDL) as well as the proportion of patients achieving a blood pressure goal of <130/80 mm Hg and proportion of patients achieving an LDL goal of <100 mg/dL.Results: For the 206 patients enrolled, the average age was 59.7 years; the majority were male (59.7%) and white (66%). When compared with baseline, the postintervention mean systolic ( P < .0001), diastolic blood pressure ( P = .0003), and LDL ( P < .0001) decreased significantly. The proportion of patients achieving a blood pressure of <130/80 mm Hg increased 21.8% ( P < .0001), and the proportion of patients achieving an LDL of <100 mg/dL increased 12% ( P = .0023).Conclusions: The results of our study indicate that collaborative management has a positive impact on decreasing cardiovascular risk and assists patients in attaining national goals for blood pressure and cholesterol.